Therapy and mechanism of natural polysaccharides for atopic dermatitis treatment - Wenjie Wang; Lijun Shao; Xiao Jiang; Qiulu Chu; Jian Xiao; Shufang Wu (Food Science and Human Wellness)
Atopic dermatitis (AD) is a common multifactorial skin disease characterized by chronic inflammation, unbearable itching, and significant physical and mental burden on patients. In recent years, there has been extensively studied on the use of natural polysaccharides in anti-inflammatory therapy, due to their low toxicity and multi-target pharmacological activity. The unique biological activities of polysaccharides from natural sources as functional food additives and cosmeceuticals present a new option for the treatment of AD. This review aims to summarize the pathogenesis of AD, the therapeutic effects, and the mechanisms of natural polysaccharides, as well as discuss the limitations and prospects of these compounds in the treatment of AD. The insights provided in this review can serve as references and inspiration for the development of applications of natural polysaccharides in the treatment of AD.